2018
DOI: 10.1002/wnan.1548
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals, challenges, and nanomedicine‐based solutions for ocular diseases

Abstract: The eye consists of sensitive, compactly adjoined tissue structures which act as strong physical (static) and physiological (dynamic) barriers that prevent entry of foreign bodies into the eye. Together, these barriers reduce the bioavailability of topically and intraocularly administered medicaments thus demanding frequent drug administration for the treatment of chronic eye diseases. Hence, development of drug delivery systems (DDS) that can be retained in ocular tissues for longer durations can help to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 252 publications
0
25
0
Order By: Relevance
“…(6) Nanocarriers improve the interactions between drugs and the cornea and conjunctival epithelium, which improve the efficiency of delivery and bioavailability of drugs. 24 , 26–28 …”
Section: Ocular Nano-drug Delivery Systemmentioning
confidence: 99%
“…(6) Nanocarriers improve the interactions between drugs and the cornea and conjunctival epithelium, which improve the efficiency of delivery and bioavailability of drugs. 24 , 26–28 …”
Section: Ocular Nano-drug Delivery Systemmentioning
confidence: 99%
“…Poorly water-soluble drugs with a strong therapeutic potential have especially benefited from nanoencapsulation, being postulated as a promising tool for circumventing the various ocular barriers. In fact, extensive research in the field has demonstrated an in-crease in drug bioavailability and residence time at ocular target tissues [45]. As a result, some products are already present in the market, such as Restasis ® [46], Ikervis ® [47] or Cequa ® [48].…”
Section: Improving Drug Access To Ocular Structures With Lipid-based mentioning
confidence: 99%
“…These systems can potentially enhance bioavailability in comparison to hydrogels without nanoparticles. Therefore, hydrogels can be utilized for intraocular or topical drug administration so as to decrease drug clearance by dynamic ocular barriers [100]. For example, for the topical administration of nanoparticles, they should be incorporated into a suspension system.…”
Section: Hydrogelsmentioning
confidence: 99%